Coordinación de protecciones en la central hidroeléctrica Río Verde Chico - Molina Salazar, Carlos Andrés (2024)
In this research work carried out at the Río Verde Chico Hydroelectric Power Plant, the current operating conditions are analyzed, simulating different scenarios in which the plant can work, in addition to simulating load flows, short-circuit currents, and the operation of the protection equipment with the current settings, In this way it was possible to know how the protection system is working, where it was possible to identify problems of misconfigured protections in the IEDs, which does not allow to have a selective protection and there are erroneous trips in the transmission lines, especially when it works in mesh, this means when it is connected to the Baños and Agoyán substation. . With this background, in chapter 3, it is proposed to make new adjustments to the protections, specifically in the protection lines, to solve in the medium and long term the problems identified, for the line distance protection zone 2 is eliminated because being short lines it is not necessary to have enabled, from the simulations performed, when there are faults at more than 80% of the transmission line the protections of the substation of arrival will act, which is the correct way to work; For the overcurrent protection, the non-directional characteristic was changed to directional in order to avoid erroneous tripping and the power plant can work in mesh; additionally, a load flow simulation was performed considering a 5% growth in demand, where it was determined that the current transformers of the lines are not designed to support the nominal current of the line when it works at full load; And for the generators, it is proposed to activate the ANSI 51V voltage controlled overcurrent protection because it is the typical and recommended recommendation for electric generators, thus guaranteeing that the protection will act in case of any unbalance in normal operation. With these new settings in the IEDs and after performing all the necessary simulations in all possible operating scenarios, it was possible to obtain a selective, reliable and fast coordination of protections against system failures.